YURIDISI PERCERAIAN DALAM PERSPEKTIF KOMPILASI HUKUM ISLAM (KHI) DI INDONESIA - Sugiarto, Eysar; Sadari, Sadari; Bahruddin, AH (Moderation | Journal of Islamic Studies Review, 2023)
Basically, in Islam justifying a husband who is going to divorce his wife is only enough to say itin front of his wife or another person (witnesses) then divorce falls, but in state life, one must obey governmentregulations, as long as they do not conflict with Islamic law itself because obedience to the government is partof the obligation as a Muslim. The government established a regulation on divorce with the aim of orderlyadministration as well as the problem of registering marriages, and childbirths and making divorce difficult.This is basically to the principles of Islamic law regarding divorce, namely making it difficult for divorce tooccur. In addition to the principle of complicating divorce, the government issued the regulation also has alegal goal that KHI (Compilation of the Islamic law) rules are in line with the concept of maqasidsyariah including at the center the principles of protecting religion, protecting the soul, protecting the mind,protecting offspring, and protecting private property rights. With the existence of these principles and concepts,the decisions of the Religious Courts in divorce cases that occur in the community become inkracht. TheCourt's decision in divorce cases is to maintain legal certainty that will occur after the divorce, namelyprotecting the rights and obligations of husband and wife, and protecting the rights of their offspring(children). Divorce if it occurs outside the court according to KHI is not justified, this is to the contents ofArticle 115 KHI which states that divorce can only be done before a court hearing after the court has triedand failed to reconcile the two parties. In terms of data collection techniques, the authors use library research,namely by studying books and journals that have something to do with the subject matter. From the resultsof the research that there are still many people who think that divorce can be done anywhere, and thishinders the renewal of Islamic law. Divorce which is carried out in front of a court session aims to realizebenefits in the form of protection for family institutions and the realization of legal certainty where marriageis not so easily broken. The KHI does not regulate the legalization of divorces that are carried out outsidethe Court. This is based on Article 115 KHI that divorce must be carried out before a court hearing.